2022
DOI: 10.7759/cureus.32622
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Medical Marijuana in Migraine Headache: A Systematic Review

Abstract: Medical marijuana treatment for migraine is becoming more common, although the legality and societal acceptance of marijuana for medical purposes in the United States have been challenged by the stigma attached to it as a recreational drug. These substances function to reduce nociception and decrease the frequency of migraine by having an impact on the endocannabinoid system. Our study reviewed the clinical response, dosing, and side effects of marijuana in migraine management. Using Preferred Reporting Items … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
(99 reference statements)
0
4
0
1
Order By: Relevance
“…Although cannabinoids have been suggested as a potential migraine treatment, the evidence about their efficacy and tolerability is lacking [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although cannabinoids have been suggested as a potential migraine treatment, the evidence about their efficacy and tolerability is lacking [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there was a substantial reduction in the use of prescribed opioids in these patients [56]. Further observational studies of patients using CBMPs have reported improvements in pain [57][58][59][60][61][62].…”
Section: Pain (Including Migraine Headaches)mentioning
confidence: 88%
“…The authors discuss a growing body of small randomized controlled clinical trials using CBD for anxiolytic effects; however, many were in healthy volunteers rather than relevant patient cohorts [72]. RWE highlights the potential value of CBMPs to reduce anxiety symptomatology and improve patients' well-being and sleep [40,56] and observational studies of CBMPs have also demonstrated improvements in anxiety [59,61,62,73]. There is a need for further investigation into which CBMPs may offer therapeutic benefits in anxiety, as well as the dosing schedule and treatment duration.…”
Section: Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…Apesar do crescente interesse e da crescente legalização em muitas partes do mundo, o uso terapêutico da Cannabis ainda é um tema controverso e sujeito a regulamentações rigorosas em muitos países. Essa controvérsia é, em parte, devido à falta de pesquisa robusta e evidências científicas claras sobre os benefícios e riscos associados ao uso da Cannabis para fins medicinais (Whiting et al, 2015;Sherpa et al, 2022).…”
Section: Introductionunclassified